1993
DOI: 10.1002/cne.903280310
|View full text |Cite
|
Sign up to set email alerts
|

Cells of origin of the spinoparabrachial fibers in the rat: A study with fast blue and WGA‐HRP

Abstract: The internal lateral (IL) subnucleus of the parabrachial nucleus (PB), which is one of the seven lateral subnuclei of the PB, receives information from the spinal cord. The IL subnucleus perhaps relays nociceptive signals to the intralaminar nuclei of the thalamus, apparently being implicated in the motivational-affective component of pain reaction. However, cells of origin of spinal fibers to the IL subnucleus have not been investigated sufficiently. We intended to clarify these cells by injection of fast blu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
54
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 56 publications
11
54
0
Order By: Relevance
“…The particular responsiveness of PBil neurons cannot be totally explained by the nociceptive input they receive from the medial and the lateral reticular portion of laminas V/VI (Kitamura et al, 1993;Bernard et al, 1995;Feil and Herbert, 1995) because most neurons recorded in laminas V/VI are nociceptive of wide dynamic range (Menétrey et al, 1977(Menétrey et al, , 1979(Menétrey et al, , 1984Dado et al, 1994), whereas most PBil neurons are nociceptive with a narrower dynamic range. There are two possible explanations.…”
Section: Figure 4 Responses Of Two Pbil-pc Neurons (One In a The Otmentioning
confidence: 99%
See 1 more Smart Citation
“…The particular responsiveness of PBil neurons cannot be totally explained by the nociceptive input they receive from the medial and the lateral reticular portion of laminas V/VI (Kitamura et al, 1993;Bernard et al, 1995;Feil and Herbert, 1995) because most neurons recorded in laminas V/VI are nociceptive of wide dynamic range (Menétrey et al, 1977(Menétrey et al, , 1979(Menétrey et al, , 1984Dado et al, 1994), whereas most PBil neurons are nociceptive with a narrower dynamic range. There are two possible explanations.…”
Section: Figure 4 Responses Of Two Pbil-pc Neurons (One In a The Otmentioning
confidence: 99%
“…1). Indeed, this nucleus receives an extensive input from nociceptive neurons in laminas V/VI of the spinal cord (Kitamura et al, 1993;Bernard et al, 1995;Feil and Herbert, 1995); it projects to the PC and to a lesser extent in other intralaminar thalamic nuclei (see also Fulwiler and Saper, 1984;Hermanson and Blomqvist, 1997b;Bester et al, 1999), and noxious stimulation evoked a marked expression of phospho-cAMP response element-binding protein in and around the PBil (Hermanson and Blomqvist, 1997a). In this study, we investigated the physiological properties of PBil neurons that project to the PC nucleus using antidromic stimulation and singleunit recording techniques.…”
mentioning
confidence: 99%
“…The LPB receives direct inputs from dorsal horn neurons of the spinal cord (Kitamura et al, 1989(Kitamura et al, , 1993Menetrey and De Pommery, 1991;Bernard et al, 1995;Feil and Herbert, 1995). Immunocytochemical staining revealed that lateral subnuclei of the LPB, which are innervated by ascending spinal afferents, exhibit axonal terminals positive for substance P (SP) (Milner et al, 1984;Milner and Pickel, 1986;Standeart et el., 1986;Block and Hoffman, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…This region is also involved in different autonomic regulatory processes (Bertrand and Hugelin, 1971;Mraovitch et al, 1982;Cechetto and Calaresu, 1983;Darlington and Ward, 1985a,b;Lumb and Morrison, 1987;Ward, 1988Ward, , 1989Ohman and Johnson, 1989;Herbert et al, 1990;Jhamandas et al, 1991;Chamberlin and Saper, 1992) and aversive behaviour (Berntson, 1973;Berntson et al, 1988;Depoortere et al, 1990a,b;Bucherelli and Tassoni, 1992;Agü ero et al, 1993;Bechara et al, 1993). The lateral and external parts of the PB area are also a major relay, transmitting nociceptive information from the lamina I neurones to either the centralis nucleus (Ce) of the amygdala or the ventromedial (VMH) nucleus of the hypothalamus (Wiberg and Blomqvist, 1984;Cechetto et al, 1985;Hylden et al, 1985Hylden et al, , 1986McMahon and Wall, 1985;Swett et al, 1985;Light et al, 1987Light et al, , 1993Tabata, 1989, 1990;Lima and Coimbra, 1989a,b;Bernard and Besson, 1990;Yamada and Kitamura, 1992;Kitamura et al, 1993;Bernard et al, 1994Bernard et al, , 1995Slugg and Light, 1994;Bester et al, 1995aBester et al, -c, 1997Feil and Herbert, 1995). More precisely, we have shown that most lamina I-PB, PB-Ce, and PB-VMH neurones respond specifically to noxious stimuli, conveyed by peripheral Ad and C fibres, and that they encode the int...…”
mentioning
confidence: 95%